ผงเมือกเมล็ดแมงลัก (Ocimum canum Sims.) และการประยุกต์ใช้ในผลิตภัณฑ์อาหาร - ศศิธร เรืองจักรเพ็ชร (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objectives of this research were to study the optimum conditions for production and to characterize the chemical and physical properties of Ocimum canum Sims. seed mucilage powder. The optimum condition for separating the mucilage were studied by using dry separation and wet separation. In dry separation, the soaking temperature (30, 60 and 90℃) and soaking time (1, 2 and 3 hrs.) of ocimum seed and grinded seed wee significantly effected (p≤0.05) on %yield and lightness value(L) of the mucilage powder. In wet separation, the soaking temperature were 30 and 60℃ , soaking time were 1, 3 and 6 hrs. and separation time were 1, 5 and 10 min. It was found that %yield was significantly increased and the L-value was significantly decreased (p≤0.05) as the increase of separation time was increased. The optimum condition for separating the mucilage can give 16.04 %yield by using wet separation process under water soaking temperature of 60℃ for 1 hr. and 10 min. separation time. Then the mucilage with low L-value was bleached by Alkaline Hydrogen Peroxide (AHP) method using 0.1, 0.3, 0.5, 0.7, 1.0 and 2.0%(w/v) H₂O₂ at pH 9.0 and 11.5 for 1, 2 and 3 hrs. The optimum condition was 2.0% (w/v) H₂O₂ at pH 9.0 for 3 hrs. The optimum temperature for drying in tray dryer was 50℃. Under such condition, the obtained mucilage powder shows good rating for white colour, water absorptability with 84.37% of total dietary fiber and less than 1% of protein and fat content. The physical characteristics of the produced mucilage power were studied by divided in two types, (1)coarse powder of ocimum gum(COG, 150-250 µm) and (2)fine powder(FOG, <150 µm). The results were compared to three gums: guar gum (GG), locust bean gum(LBG) and xanthan gum(XG). It was found that the COG type showed lower L-value and worse oil absorptability than the FOG type, but higher in viscosity and emulsion capacity. Moreover, the ocimum powder solution had Newtonian flow behavior at low concentration and pseudoplastic flow at high concentration (<0.5% w/v) which was similar to that of GG and XG solution. The change in sucrose concentration and pH had no effect on viscosity of all gum solutions but its viscosity was decreased throughout the increase of temperature, shear rate and NaCl concentration which was the same as that of GG solution. The COG and FOG type had synergistic effect with GG and XG. When the COG type was added in low-fat mayonnaise to replace the egg yolks at 0.3, 0.5, 0.7 and 1.0% concentrations, the added mayonnaise had lower viscosity than the commercially available low-fat mayonnaise. Addition of the COG type at 0.7-1.0% concentrations was not found the separation of the mayonnaise emulsion within 2 months.